Dual constraints on synapse formation and regression in schizophrenia: neuregulin, neuroligin, dysbindin, DISC1, MuSK and agrin - Bennett A O, Maxwell R (Australian and New Zealand journal of psychiatry, 2008)
During adolescence there is a loss of approximately 30% of the synapses formed in the cortex during childhood. Comprehensive studies of the visual cortex show that this loss of synapses does not occur as a consequence of less appropriate projections being eliminated in favour of more appropriate ones. Rather it seems that synapses with low efficacy for transmission are eliminated in favour of those with higher efficacy. The loss of low-efficacy synapses is known, on theoretical grounds, to enhance the function of neural networks, but large synapse losses lead to failure of network function. In the dorsolateral prefrontal cortex (DLPC) of those suffering from schizophrenia the number of synapses is relatively very low, approximately 60% lower than that observed in normal childhood. It is not known if this is due to an additional loss over that during normal adolescence or whether it results from a failure to form a normal complement of synapses during childhood. The first study of synapse loss in the mammalian nervous system was made on the neuromuscular junction at Sydney University in 1974. Since then this junction has provided principal insights into the molecular basis of synapse formation and regression, so providing a paradigm for investigations of these phenomena in the DLPC. For example the molecules muscle-specific receptor tyrosine kinase (MuSK), agrin and neuregulin have been identified and their critical roles in the formation and maintenance of synapses elucidated. Loss of function of MuSK or agrin leads to failure of neuromuscular synapse formation as well as a loss of approximately 30% of excitatory synapses in the cortex. Similar synapse loss occurs on failure of neuregulin in vitro and of neuroligin in vivo. It is suggested that three important questions need to be answered: first, over what development period are the synapse numbers in DLPC of subjects with schizophrenia lower than normal; second, what are the relative importance of MuSK/agrin, neuregulin/ErB and neurexin/neuroligin in synapse formation and regression in the DLPC; and third, to what extent have these molecules gone awry in schizophrenia.